THE EFFECT OF MEMORIZING AL-QUR’AN ON ADOLESCENT SELF CONTROL IN RQT AL-MUKMIN - Dzikra Daffa Salsabela; Afif Khairullah; Aldi Alisin; Nova Zahrani; Rati Oktariasni (CV. Doki Course and Training, 2023)
This research was conducted to determine the effect of memorizing Al-Qur'an on self-control possessed by adolescents. The research method used is experimental research with one group pre-test posttest design. The sampling procedure used purposive sampling technique which consisted of 30 students as the experimental group. The experimental group will be given treatment in the form of memorizing surah in Al-Qur'an. The data collection method used is the Likert model scale regarding self-control scale. Data analysis in this study used statistical applications, namely SPSS with t-test with independent samples test analysis through pre-test and postest. By using SPSS a significant value of 0.017 was obtained and Ho was rejected and Ha was accepted.